2010
DOI: 10.1159/000322888
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Mapping of the Retroelements <i>Rex1, Rex3</i> and <i>Rex6</i> among Cichlid Fish: New Insights on the Chromosomal Distribution of Transposable Elements

Abstract: To enhance our understanding of the organization of the genome and chromosome evolution of cichlid fish species, we have isolated and physically mapped onto the chromosomes the transposable elements (TEs) Rex1, Rex3 and Rex6, which are conserved in teleost fish, in the chromosomes of African and South American cichlid species. The physical mapping of different Rex elements showed that they are primarily compartmentalized in the pericentromeric heterochromatic regions, although dispersed or clustered signals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 133 publications
9
89
0
Order By: Relevance
“…The analysis of different Rex elements revealed that they are compartimentalized in pericentromeric heterochromatic regions, suggesting that these elements are part of the structure and organization of heterochromatic areas. 34,35 Similar data on the organization of Rex elements was observed in Perciformes, representatives of the Antartic fish as in the species Notothenia coriiceps. 33 In the family Cichlidae, more specifically in the genome of the Nile Tilapia Oreochromis niloticus, besides the Rex elements 35 several other TEs, such as the LINE CiLINE2, 36 non-LTR On2318 and Tc1-like On239, 37 SINE ROn-1, 38,39 and ROn-2 39 have been encountered.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The analysis of different Rex elements revealed that they are compartimentalized in pericentromeric heterochromatic regions, suggesting that these elements are part of the structure and organization of heterochromatic areas. 34,35 Similar data on the organization of Rex elements was observed in Perciformes, representatives of the Antartic fish as in the species Notothenia coriiceps. 33 In the family Cichlidae, more specifically in the genome of the Nile Tilapia Oreochromis niloticus, besides the Rex elements 35 several other TEs, such as the LINE CiLINE2, 36 non-LTR On2318 and Tc1-like On239, 37 SINE ROn-1, 38,39 and ROn-2 39 have been encountered.…”
supporting
confidence: 63%
“…34,35 Similar data on the organization of Rex elements was observed in Perciformes, representatives of the Antartic fish as in the species Notothenia coriiceps. 33 In the family Cichlidae, more specifically in the genome of the Nile Tilapia Oreochromis niloticus, besides the Rex elements 35 several other TEs, such as the LINE CiLINE2, 36 non-LTR On2318 and Tc1-like On239, 37 SINE ROn-1, 38,39 and ROn-2 39 have been encountered. In O. niloticus, these TEs are found generally dispersed in the genome and may also be related to sex differentiation within this species.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…4C). A. hasemani contains terminal sites on pairs 2, Z, 5,8,12,13,18,20,24,26,27 and at the terminal region on the short arm of the W chromosome (Fig. 4D).…”
Section: Physical Chromosome Mapping Of Repetitive Dnasmentioning
confidence: 99%
“…However, reassociation kinetics based on C o t-1 DNA and the microdissection of chromosomes submitted to C-banding and the subsequent amplification of heterochromatic sequences using degenerate oligonucleotide-primed polymerase chain reaction (PCR) have been used successfully. [9][10][11][12][13][14] The Parodontidae is a Neotropical fish group that is divided into three genera: Parodon, Apareiodon, and Saccodon. 15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites.…”
mentioning
confidence: 99%